ELECTRONIC INFORMATION SYSTEMS IN MEDICINE AND BIOLOGY: GENERAL ANALYSIS - O. M. Klyuchko (Medična Informatika ta Inženerìâ, 2020)
Background. In present publication we generalized and analyzed the experience of electronic information systems with databases use in medicine and biology, as well as classified observed versions of modern medical and biological information systems for the use of this knowledge for the construction of new information systems.